Impact of A Local Food-Based Isotonic Beverage on Post-Exercise Heart Rate in Adolescent Soccer Players in Karawang - Linda Riski Sefrina; Ratih Kurniasari (Fakultas Kedokteran Universitas Sultan Ageng Tirtayasa, 2025)
The performance of soccer players is affected by their condition, including hydration status. Previous studies have shown that the level of dehydration in adolescent soccer players was very high. Therefore, a strategy was needed to prevent dehydration in soccer players. The purpose of this study was to identify the isotonic effect of using local food ingredients (cucumber, lemon, honey) on the heart rate of adolescent soccer players. The design of this study was a pre-experimental one-shot case study, with a total of 25 participants divided into the Local Food Isotonic (LFI) group and the Commercial Isotonic (CI) group. The results of this study showed that the nutritional content of LFI was similar to CI. The heart rate in the LFI group was significantly different compared to the CI group (p-value=0.005). Therefore, local food isotonic can be used as an alternative isotonic to prevent dehydration and maintain the performance of soccer players. Further research is expected to provide a control group and other variables related to cardiovascular indicators and player performance.